1982
DOI: 10.1126/science.216.4548.821
|View full text |Cite
|
Sign up to set email alerts
|

Amazon Basin Soils: Management for Continuous Crop Production

Abstract: Technology has been developed which permits continuous production of annual crops in some of the acid, infertile soils of the Amazon Basin. Studies in Yurimaguas, Peru, show that three grain crops can be produced annually with appropriate fertilizer inputs. Twenty-one crops have been harvested during the past 8(1/2) years in the same field, with an average annual production of 7.8 tons of grain per hectare. Soil properties are improving with continuous cultivation. The technology has been validated by local fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
101
1
18

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(123 citation statements)
references
References 14 publications
3
101
1
18
Order By: Relevance
“…Previous studies have reported that leaves of this hybrid have artemisinin levels in the range 0.8-1.2% (Magalhães et al 1997, Marchese et al 2001. No large variation in the levels of artemisinin among the hybrids in the three Amazonian ecosystems was observed despite the rather large differences in the nutritional composition of soils of the várzea, terra preta de índio and terra firme areas (Sanchez et al 1982). The levels of artemisinin found in these hybrids cultivated in the Amazon are similar to those found in the standardised and stabilised plants from Paulínia from which the Amazon hybrids are derived.…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies have reported that leaves of this hybrid have artemisinin levels in the range 0.8-1.2% (Magalhães et al 1997, Marchese et al 2001. No large variation in the levels of artemisinin among the hybrids in the three Amazonian ecosystems was observed despite the rather large differences in the nutritional composition of soils of the várzea, terra preta de índio and terra firme areas (Sanchez et al 1982). The levels of artemisinin found in these hybrids cultivated in the Amazon are similar to those found in the standardised and stabilised plants from Paulínia from which the Amazon hybrids are derived.…”
Section: Discussionsupporting
confidence: 57%
“…Efeitos benéficos do manejo orgânico de solos ácidos têm sido observados em diversos sistemas agrícolas, cujas principais alterações químicas na camada de 0 a 20 cm de profundidade são: elevações do pH e do teor de Ca em detrimento do Al (Sanchez et al, 1982;Hue & Amien, 1989;Bessho & Bell, 1992). Em alguns casos, esses efeitos se estendem à subsuperfície do solo (Watt et al, 1991;Pavan, 1994;Liu & Hue, 1996;Oliveira & Pavan, 1996).…”
Section: Introductionunclassified
“…Os principais fatores para que isso ocorra são: baixa fertilidade do solo, com elevada acidez e baixa soma de bases (SANCHEZ et al, 1982;MOREIRA e FAGERIA, 2009) brasiliensis), a presença do fungo Microcyclus uley (mal-das-folhas) reduz significativamente a produção de látex (GASPAROTTO et al, 1997).…”
Section: Introductionunclassified